ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA PENGELOLAAN PENYEDIAAN AIR BERSIH PERDESAAN DI DESA BUKIAN GIANYAR - Adnyana, Ida Bagus Putu; Sila Dharma, I Gusti Bagus; Dwipa Arta, I Made (JURNAL SPEKTRAN, 2019)
ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF CLEAN WATER SUPPLY MANAGEMENT IN VILLAGE BUKIAN GIANYAR ABSTRACT The developmemt of clean water infrastructures and facilities in rural areas has not been accessed properly. By using PANSIMAS program from the goverment and communityself - help, it has been constructed drinking water infrastructures and facilities that will be managed by community itself by forming Management Facility Group (KPS). The limitation of management capability causes problems in implementation of management so that the water management perfomance tends to decrease. So it is necessary to conduct  a research toanalyze the factors that affect the perfomance of clean water management in Bukian Village, Payangan District, Gianyar Regency. This research was conducted through interview technique by using questionnaire and analyzed using factor analysis. Research variabels to be analyzed consisted 55 (fifty five) variabels from five aspects of public sector performance measurement (aspect of input, process, output, outcome and impact) which cover 9 (nine) dimensions based on literature reviews and 5 (five) dimensions based on interview results. The test result of the research instruments was begun with the validity and reliability test. The factor analysis was stated feasible and there was a variable correlation. Partial correlation testing stage used MSA to measure the correlation of all variables. From the analysis result to 55 research variables, there were 21 variables that were reduced, so there were 34 research variables to do analysis again. Furthermore, the main component analysis was done to reduce data to be simpler with the result of factor extraction for the management performance of clean water supply amounted to 9 new factors. The dominant factor which affects the management performance of water supply is the factor of service improvement.Based on the conclusion of the research results is suggested to create a legal policy in the form of Local Regulations (Perda) of rural water management. It takes the role of the village apparatus as a SPAM’s counselor in the form of commitment and support to legality and independence of UPS/KPS in the local village.